Micropapillary carcinoma in a dog: case report - Estrada, Cristhian Rene Vargas; Firmo, Bruna Fernanda; Maronezi, Marjury Cristina; Faro, André de Mattos; Vela, Daniele Belchior; Silva, Mariana Palma Correa da; Moi, Tryssia Scalon Magalhães; Alcântara, Brenda Mendonça de; Bonato, Letícia; Huppes, Rafael Ricardo; et al. (Medicina Veterinária, 2021)
Mammary neoplasms in female dogs have a high incidence. Among the several histological types observed, micropapillary carcinoma is considered one of the most aggressive due to vascular invasion, metastases, and short survival time. The present objective was to describe a case of mammary gland micropapillary carcinoma, with cutaneous metastasis, in a dog. A 14-year-old intact nulliparous mixed-breed bitch, weighing 8kg, with a history of pseudocyesis and no history of contraceptive administration, presented to the Veterinary Reproduction and Obstetrics Service from "Governador Laudo Natel” Hospital, FCAV, UNESP, Jaboticabal, with an ulcerated nodule in the mammary gland for approximately one month. After stabilization of clinical parameters and preoperative exams, a radical unilateral mastectomy and ipsilateral axillary and inguinal lymphadenectomy were performed. Histopathology revealed micropapillary carcinoma with clear surgical margins, however, there were metastases in both lymph nodes. Antineoplastic chemotherapy was refused by the owners. On the 60th day after surgery, there was an inflammatory reaction in the surgical scar region, with a small cutaneous ulceration, where elastography showed rigidity and shear velocity of 7.84m/s. Skin biopsy revealed metastasis of the micropapillary carcinoma. Even with continued treatment since the patient was first examined, the ulcerations progressed, compromising the animal’s welfare and physiological activities, and on the 110th day after surgery, euthanasia was decided on. A correct diagnosis and knowledge of tumor biological behavior are important points for choosing the correct treatment. Acoustic Radiation Force Image (ARFI) elastography has been shown to be a fast and non-invasive diagnostic method for detection of recurrent micropapillary carcinoma.